Differences Between Exergaming Rehabilitation and Conventional Physiotherapy on Quality of Life in Parkinson's Disease: A Systematic Review and Meta-Analysis - Elena, Papamichael; Demetris, Solou; Christina, Michailidou; Marios, Papamichail (Frontiers in Neurology, 2021)
Parkinson’s Disease is a neurodegenerative condition with both motor and non-motor symptoms affecting the quality of life of older adults. Exergaming rehabilitation allows the interaction of the subject with digital games through the implementation of repetitive functional activities. Conventional physiotherapy uses patient centered programs that include a variety of active exercises. The aim of this review was to look into the effectiveness of exergaming rehabilitation on the quality of life of people with Parkinson’s Disease and compare it with conventional physiotherapy. Five electronics databases were searched for eligible studies until February 2021. For the statistical analysis, the mean, the standard deviation and 95% confidence interval were used to calculate effect sizes between groups. To determine heterogeneity statistical index Ι² were used. A total of 548 participants were included in 14 studies. Exergaming Rehabilitation related with improved quality of life (p= 0,687, 95% CI -1.682 - -0.734), balance (p= 0.039, 95%CI 0.364 – 13.689), (p=0.018, 95% CI 0.446 – 4.830) and gait (p=.005, 95% CI 0.351 – 1.924). No significant deference was found between groups regarding the Unified Parkinson Disease Rating Scale (p=0.196, 95% CI -5.970 – 1.225) and for the Time Up and Go Test (p=0.12, 95% CI 0.446 – 4.830). Exergames as a rehabilitation method can be used to provide alternative interactive intervention with positive results for quality of life in people with Parkinson. Further investigation is needed to assess the effect on mental health in this population group.